Essential Oil Composition of Two Grammosciadium DC Species, G. platycarpum (Boiss et Hausskn) Schischk and G. macrodon Boiss (Apiaceae), from Turkey - Yuce, Ebru; Paksoy, Mehmet Yavuz; Bagci, Eyup (Pharmacotherapy Group, 2016)
Purpose: To investigate and compare the essential oil composition of two Grammosciadium species obtained by hydrodistillation Methods: The essential oil of the aerial parts of two species was obtained by hydrodistillation and analyzed by gas chromatography (GC) and gas chromatography - mass spectrometry (GC-MS). Results: In G. platycarpum, twenty-seven compounds were identified representing 99.3 % of the total oil. The major constituents of the oil were limonene (28.4 %), beta-pinene (16.1 %), beta-selinene (15.9 %), delta-3-carene (11.2 %), alpha-farnesene (6.0 %) and p - cymene (4.7 %). The oil of G. macrodon contained thirty-seven components representing 94.4 % of the total oil, with caryophyllene oxide (15.9 %), germacrene - D (12.4 %), beta-caryophyllene (11.5 %), delta-3 - carene (10.1 %) and cyclohexane (4.6 %) as the main constituents. Conclusion: The essential oil composition of G. macrodon was analysed for the first time, the most abundant constituents being caryophyllene oxide, and cyclohexane.
Keywords: Grammosciadium macrodon; Grammosciadium platycarpum; Essential oil; Limonene; Caryophyllene oxide; Germacrene - D; beta-Caryophyllene; delta-3-Carene